Plasma biomarkers: new non-invasive tests in the early diagnosis of colorectal cancer? - Alpaca, Hugo (2022)
Colorectal cancer (CRC) is the second leading cause of cancer death in the United States and Europe. In Peru, it ranks fourth for both incidence and mortality. Colonoscopy is the gold standard for screening tests, showing high sensitivity and specificityto identify polyps and cancer (> 98 %). However, it is an invasive procedure, which should be repeated at certain intervals, is expensive, and has low compliance rates and a perforation risk of 1 per 1,000 to 10,000. These limitations make it useless as an early detection tool in terms of implementation costs in many countries. An alternative is the use of plasma tumor biomarkers, which are molecular products metabolized and secreted by neoplastic tissue. These tests are based on proteins or nucleic acids,and represent a tool for the early detection, prognosis, survival and prediction of the response to CRC treatment. The objective of this research work is to analyze the usefulness of protein-based plasma biomarkers for the early detection of CRC. Moreover,a combination of biomarkers that includes carcinoembryonic antigen, cyclooxygenase 2, tissue inhibitor of metalloproteinase-1 and p53 autoantibodies is proposed to maximize the benefits of early detection of premalignant lesions and colorectal cancer, and minimize the number of patients with false-positive results and invasive procedures with potential complications.